OP0066 Targeting the Lowest Efficacious Dose for Rheumatoid Arthritis Patients in Remission: Clinical and Structural Impact of a Step-Down Strategy Trial Based on Progressive Spacing of TNF-Blocker Injections (Strass Trial). (23rd January 2014) - Fautrel, B.; Gandjbakhch, F.; Foltz, V.; Pham, T.; Morel, J.; Alfaiate, T.; Dernis, E.; Gaudin, P.; Mariette, X.; Tubach, F.
Abstract : Background: Biologic tapering has been associated to relapse or structural damage progression in rheumatoid arthritis (RA). Objectives: To compare the impact of a DAS28-driven step-down strategy based on TNF-blocker injection spacing (S arm) to a maintenance strategy (M arm) in an equivalence RCT conducted in established RA patients in DAS28 remission with etanercept (ETA) or adalimumab (ADA). Methods: Inclusion criteria were: ETA or ADA > 1 year, DAS28 remission > 6 months, stable damage on X-rays. Patients were randomized and followed 3-monthly for 18 months. In the S arm, the inter-injection interval was increased every 3 months up to full stop at 4th step. If DAS28 remission was lost, tapering was reversed to the previous step. Hand and foot X-rays at baseline and 18 months. Study endpoints were disease activity (DAS28), relapse (ΔDAS28>0.6 + DAS28>2.6), and X-ray damage assessed by vdH-SHS (2 independent readers, blinded of patient characteristics and treatment arm). Progression was defined as ΔvdH-SHS>1. Results: 137 patients were included, 64 and 73 in the S and M arm (mean/%: age 55 yrs, female 78%, RA duration 9.5 yrs, RF+ 68%, ACPA+ 78%, erosive 88%, DAS28 1.8, DAS44 1.0, ETA 54 %, ADA 46 %). At 18 months, 47 (73.4%) patients of the S-arm tapered TNF-blockers, of whom 24 (37.5%) stopped. Mean DAS28 and mean HAQ were not significantly different between arms. Relapse occurred at least once more frequently in the S than in the M arm (81% vs. 56%, p=0.0009) (Figure). Structural damage progression was not significantly different between arms (p=0.3) (Figure). Only 4 (6.7%) and 3 (4.5%) patients progressed in the S and M arms. Image/graph: Conclusions: Although relapses were more frequent, the Spacing strategy results in non-significant increase of disease activity and functional impairment, with no significant structural progression. Target the lowest efficacious dose in RA in remission may be considered as the new paradigm for such patients (ClinicalTrials.gov n°: NCT00780793 ). Disclosure of Interest: None Declared